Breeding Biology of Freshwater Goby Glossogobius Giuris Using Gonadosomatic Index and Gonadal Histology (Annals of Bangladesh Agriculture, 2020)
The breeding season of fishes plays an important role in fish domestication and conservation of fish diversity. Freshwater goby, Glossogobius giuris is an important food fish of Bangladesh. Therefore, a study was performed to determine the breeding biology through assessing the gonadosomatic index (IG), fecundity and histology of gonad of G. giuris. A total of 1371 females and 1051 male fishes were collected from the Belai beel of Gazipur district. Significantly (P